Improving Student Learning Interest in Islamic Religious Education Through the Implementation of Jigsaw Cooperative Learning Model at SMK Negeri 7 Tanjung Jabung Barat - Muhammad Saufi, Yuliana Afifah (Lembaga Bale Literasi, 2025)
This study investigates the effectiveness of the Jigsaw cooperative learning model in improving students' learning interest in Islamic Religious Education (PAI) at SMK Negeri 7 Tanjung Jabung Barat. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart cycle model, the study was conducted in two cycles involving 30 XI-students during the 2025/2026 academic year. Data were collected through Likert-scale questionnaires, classroom observation sheets, formative tests, interviews, and documentation. The data were analyzed using descriptive statistical techniques and the qualitative analysis model of Miles and Huberman. The findings revealed significant improvements across all measured dimensions. The average learning interest score increased from 52.4 in the pre-cycle stage to 82.5 in Cycle II, representing a cumulative improvement of 57.4%. Student activity levels rose from 30.0% to 85.3%, while the percentage of students achieving the Minimum Completeness Criterion (MCC) increased substantially from 30.0% to 90.0%. Student responses also indicated a highly positive perception of the Jigsaw model, with an average positive response rate of 86.0%. These findings demonstrate that the Jigsaw cooperative learning model effectively promotes autonomy, competence, and social connectedness the three fundamental components of intrinsic motivation thereby making it an effective, evidence-based, and pedagogically sound instructional strategy for Islamic Religious Education in vocational secondary schools.